An experimental study on thermal effects in building integrated semi transparent double skin façades for a nearly zero energy building - Gur, Muhammed; Öztop, Hakan Fehmi; Yamac, Halil Ibrahim; Gurgenc, Ezgi; Selimefendigil, Fatih (Pergamon-Elsevier Science Ltd, 2026)
An experimental study has been performed to evaluate the thermal behavior of a naturally ventilated double-skin fa & ccedil;ade (DSF) integrating semi-transparent monocrystalline PV modules on the east, south, and west fa & ccedil;ades of a nearly zero energy building in Elaz & imath;g, T & uuml;rkiye. The 18 cm cavity with seasonally operated vents was assessed through the cavity outdoor temperature difference (Delta T) and degree-hour integrals. In winter, the cavity remained 3-6 degrees C warmer, yielding 70-135 degrees C & sdot;h heating gains. Spring maintained positive Delta T, dominated by east morning and west afternoon effects. Summer showed limited cooling in June and net heating in July-August, while autumn regained strong heating (95-106 degrees C & sdot;h). Orientation analysis identified east-morning, southmidday, west-afternoon dominance. Accordingly, vents should remain closed in winter and open in summer. Annual results show 2.43 MWh on site electricity generation, 1.457 tCO2 avoided emissions, and USD 114 benefit, demonstrating the potential of orientation-aware fa & ccedil;ades for climate adaptive, energy efficient building design. Importantly, the presented field-measurement methodology and the degree-hour based performance indicators are not limited to the investigated building; they can be adopted to evaluate and optimize PVintegrated double-skin fa & ccedil;ades across different orientations, climates, and retrofit scenarios, enabling practical engineering applications in high-performance building design.
Keywords: Nearly zero energy buildings; Building integrated semi transparent photovoltaics; Fa & ccedil;ade; Renewable energy; Energy efficiency